Digitalization Processes in A Pharmaceutical Company - Xu Chaoqun; Elena Kolganova (Communications of International Proceedings, 2021)
In the face of the challenges of the new era, Chinese pharmaceutical companies were forced to quickly restructure the work of enterprises in a very short time, not only increasing production volumes, but also increasing the share of digital technologies. Among them is the Chinese pharmaceutical company Shuanghuaiji Pharmaceutical Co. Ltd., which has relied on digital technologies in the changed economic reality. Digital transformation has covered all segments of the pharmaceutical market, and how effectively new technologies are used will determine the future of a pharmaceutical company, its competitiveness and the level of drug supply for the population.
Keywords: pandemic; pharmaceutical industry; digital technologies; digital economy; digitalization; business processes.